2013
DOI: 10.1017/s002205071300034x
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal World Portfolio on the Eve of World War I: Was There a Bias to Investing in the New World Rather Than in Europe?

Abstract: International audienceThe geographical distributions of French and British foreign investment portfolios differ markedly before World War I. Did French portfolios favor European investments just as British portfolios favored “New World” assets? Should economic rationality have encouraged investors to invest widely in the “New World” rather than in Europe? Combining Modern Portfolio Theory and a new data set comprising assets listed on the Paris and London Stock Exchanges, we show that investing in the “New Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…25 See Goetzman and Ukhov (2006) and Chabot and Kurz (2010). On the contrary, Edlinger et al (2013) argue that, while diversifying, British investors at the LSE showed a foreign bias.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…25 See Goetzman and Ukhov (2006) and Chabot and Kurz (2010). On the contrary, Edlinger et al (2013) argue that, while diversifying, British investors at the LSE showed a foreign bias.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Assets from the United States seem to yield a higher return than average. Looking at the last column of the table, the same is true for France (note that Edlinger, Merli and Parent (2013) do not provide returns on French debt). This is evidence that Britain benefited from a pure exorbitant privilege.…”
Section: Previous Studies On Returnsmentioning
confidence: 86%
“…Taking our analysis one step further, we considered a risk-averse investor who follows the Modern Portfolio Theory principles, and specifically applies the Capital Asset Pricing Model (Sharpe, 1963;Lintner, 1965;Mossin, 1966). A classical methodology is implemented to test the rationality of investments, as used by Goetzmann and Ukhov (2006) or Edlinger, Merli, and Parent (2013). The idea is that if investors used monthly returns from January 1903 to December 1912 to form their risk/return expectations for January 1913, the mean variance solution would maximize their utility and would be superior ex post to any other advised recommendation.…”
Section: Advised Versus Optimal Portfoliosmentioning
confidence: 99%
“…During the decades preceding the First World War, Great Britain and France were at the forefront of huge international capital flows (Woodruff, 1966;Fishlow, 1985;Goetzmann & Ukhov, 2006;Edlinger, Merli, & Parent, 2013). There were almost as many foreign issues as domestic issues on the Parisian market between 1900 and 1914 and on the eve of the First World War, the Paris Stock Exchange had fully developed, giving French investors wide access to many different securities issued by public or private issuers from not only European countries but also more distant nations.…”
Section: Introductionmentioning
confidence: 99%